### All SAT Math Resources

## Example Questions

### Example Question #1 : Quadratic Equations

Solve: x^{2}+6x+9=0

**Possible Answers:**

9

3

6

12

-3

**Correct answer:**

-3

Given a quadratic equation equal to zero you can factor the equation and set each factor equal to zero. To factor you have to find two numbers that multiply to make 9 and add to make 6. The number is 3. So the factored form of the problem is (x+3)(x+3)=0. This statement is true only when x+3=0. Solving for x gives x=-3. Since this problem is multiple choice, you could also plug the given answers into the equation to see which one works.

### Example Question #1 : How To Factor The Quadratic Equation

64x^{2} + 24x - 10 = 0

Solve for x

**Possible Answers:**

**Correct answer:**1/4 and -5/8

64x^{2} + 24x - 10 = 0

Factor the equation:

(8x + 5)(8x – 2) = 0

Set each side equal to zero

(8x + 5) = 0

x = -5/8

(8x – 2) = 0

x = 2/8 = 1/4

### Example Question #1 : Quadratic Equations

All of the following functions have a exactly one root EXCEPT:

**Possible Answers:**

f(x) = 9x^{2} – 6x + 4

f(x) = (1/4)x^{2} + x + 1

f(x) = x^{2} – 2x + 1

f(x) = 4x^{2 }– 4x+1

f(x) = (–1/9)x^{2} + 6x – 81

**Correct answer:**

f(x) = 9x^{2} – 6x + 4

The roots of an equation are the points at which the function equals zero. We can set each function equal to zero and determine which functions have one root, and which does not.

Another piece of information will help. If a quadratic function has one root, then it must be a perfect square. This is because a quadratic function that is a perfect square can be written in the form (x – a)^{2}. If we set (x – a)^{2} = 0 in order to find the root, we see that a is the only value that solves the equation, and thus a is the only root. Additionally, a quadratic equation is a perfect square if it can be written in the form a^{2}x^{2} + 2abx + b^{2} = (ax + b)^{2}.

Let's examine the choice f(x) = 4x^{2 }– 4x+1. To find the roots, we set f(x) = 0.

4x^{2 }– 4x+1 = 0

We notice that 4x^{2 }- 4x + 1 is a perfect square, since we could write it as (2x – 1)^{2}. Thus, this equation has only one root, and it can't be the answer.

If we look at f(x) = x^{2} –2x + 1, we see that x^{2} – 2x + 1 is also a perfect square, because it could be written as (x – 1)^{2}. This function also has a single root.

Next, we examine f(x) = (1/4)x^{2} + x + 1. Let us set f(x) = (1/4)x^{2} + x + 1 = 0.

(1/4)x^{2} + x + 1 = 0

We can multiply both sides by four to get rid of the fraction.

x^{2 }+ 4x + 4 = 0

(x + 2)^{2} = 0

This function is also a perfect square and has a single root.

Now consider the choice f(x) = (–1/9)x^{2} + 6x – 81.

f(x) = (–1/9)x^{2} + 6x – 81 = 0

Multiply both sides by –9.

x^{2 }– 54x + 729 = 0

(x – 27)^{2} = 0.

Finally, let's look at f(x) = 9x^{2} – 6x + 4. This CANNOT be written as a perfect square, because it is not in the form a^{2}x^{2} + 2abx + b^{2} = (ax + b)^{2}. It might be tempting to think that 9x^{2} - 6x + 4 = (3x - 2)^{2}, but it does NOT, because (3x – 2)^{2} = 9x^{2} – 12x + 4. Therefore, because 9x^{2} – 6x + 4 is not a perfect square, it doesn't have exactly one root. ^{}

### Example Question #1 : How To Factor The Quadratic Equation

The difference between a number and its square is 72. What is the number?

**Possible Answers:**

14

19

30

18

9

**Correct answer:**

9

x^{2} – x = 72. Solve for x using the quadratic formula and x = 9 and –8. Only 9 satisfies the restrictions.

### Example Question #192 : Algebra

Given and , find the value of .

**Possible Answers:**

**Correct answer:**

We can factor the quadratic equation into .

Then we can see that .

Therefore, becomes and .

### Example Question #1 : Quadratic Equations

Which of the following is a root of the function ?

**Possible Answers:**

**Correct answer:**

The roots of a function are the *x* intercepts of the function. Whenever a function passes through a point on the *x*-axis, the value of the function is zero. In other words, to find the roots of a function, we must set the function equal to zero and solve for the possible values of *x*.

This is a quadratic trinomial. Let's see if we can factor it. (We could use the quadratic formula, but it's easier to factor when we can.)

Because the coefficient in front of the is not equal to 1, we need to multiply this coefficient by the constant, which is –4. When we mutiply 2 and –4, we get –8. We must now think of two numbers that will multiply to give us –8, but will add to give us –7 (the coefficient in front of the *x* term). Those two numbers which multiply to give –8 and add to give –7 are –8 and 1. We will now rewrite –7x as –8x + x.

We will then group the first two terms and the last two terms.

We will next factor out a 2*x* from the first two terms.

Thus, when factored, the original equation becomes (2*x *+ 1)(*x –* 4) = 0.

We now set each factor equal to zero and solve for *x*.

Subtract 1 from both sides.

2*x* = –1

Divide both sides by 2.

Now, we set *x* – 4 equal to 0.

*x* – 4 = 0

Add 4 to both sides.

*x* = 4

The roots of *f*(*x*) occur where *x* = .

The answer is therefore .

### Example Question #1 : Quadratic Equations

36x^{2} -12x - 15 = 0

Solve for x

**Possible Answers:**

1/2 and 5/6

-1/2 and 5/6

1/2 and 1/3

-1/2 and -5/6

1/2 and -1/3

**Correct answer:**

-1/2 and 5/6

36x^{2} - 12x - 15 = 0

Factor the equation:

(6x + 3)(6x - 5) = 0

Set each side equal to zero

6x + 3 = 0

x = -3/6 = -1/2

6x – 5 = 0

x = 5/6

### Example Question #1 : Quadratic Equations

Find the roots of the equation .

**Possible Answers:**

**Correct answer:**

To factor this, we need to find a pair of numbers that multiplies to 6 and sums to 5. The numbers 2 and 3 work. (2 * 3 = 6 and 2 + 3 = 5)

(*x* + 2)(*x* + 3) = 0

*x* = –2 or *x* = –3

### Example Question #1 : Quadratic Equations

In the equation , what are the values of ?

**Possible Answers:**

None of the other answers

**Correct answer:**

To solve, begin by setting the equation to 0. Then factor the equation. We know that in our two factors, one will begin with and one will begin with . Fiddling with different factors of (we are looking for two numbers that, when multiplied by and separately, will add to ), we come to the following:

(If you are unsure, double check by expanding the equation to match the original)

Now, set the each factor equal to 0:

Do the same for the second factor:

Therefore, our two values of are and .

Alternatively, this problem can be solved by plugging each answer choice into the original equation and finding which set of numbers make the equation equate to 0.

### Example Question #10 : Quadratic Equations

Solve for :

**Possible Answers:**

and

and

and

and

and

**Correct answer:**

and

To solve for , we need to factor the equation to identify its roots, or the values of that make the equation equal .

We can factor out a from each of the terms on the left side of the equation since they have that in common:

Then, we can factor the remaining quadratic portion of the equation. and have a difference of , suggesting that trying and might work:

At this point, we can identify the roots of the equation by setting and and solving each of these equations to yield and , respectively.